Bottom gate top contact organic transistors using thiophene and furan flanked diketopyrrolopyrrole polymers and its comparative study. (1st September 2022) - Do, Thu-Trang; Takeda, Yasunori; Sekine, Tomohito; Yadav, Yogesh; Manzhos, Sergei; Feron, Krishna; Singh, Samarendra P; Tokito, Shizuo; Sonar, Prashant
Abstract: Herein, two donor–acceptor conjugated polymers based on dithieno[3, 2- b :2′, 3′- d ]thiophene (DTT) and thiophene-flanked diketopyrrolopyrrole (DPP) or furan-flanked DPP, namely PDPPT-DTT and PDPPF-DTT were synthesised, characterised and evaluated for their electrical performance in transistor devices for comparison. The influence of the heteroatoms (thiophene and furan) flanked DPP on their thermal, optical, electronic structure and charge carrier transport properties were investigated. The absorption spectra of polymer PDPPT-DTT are broader and red-shifted (26–30 nm) compared with that of polymer PDPPF-DTT, indicating the resonance energy of thiophene is greater than furan, which may allow for different electron localization and result in the difference of optical properties. In addition, energy levels of polymers were slightly affected by the aromatic remote end-groups (thiophene to furan) in DPP-based molecule. Hole transport properties of copolymers were investigated by fabricating the field-effect transistors in the bottom gate top contact (BGTC) configurations for three different self-assembled monolayers (SAMs)/gate dielectric interfaces and different annealing temperatures of polymeric active layer. The BGTC organic thin film transistor (OFET) devices having PDPPT-DTT and PDPPF-DTT thin film annealed at 200 °C exhibit the hole mobility of 0.18 and 0.20 cm 2 V −1 s −1, respectively. The OFET devices with trichloro(octyl)silane SAM, fabricated and characterized in ambient environment (temperature ∼25 °C, humidity ∼50%), were found to retain 90% of their performance up to 1000 h.